PENGARUH PARTISIPASI ANGGARAN DAN KETERLIBATAN KERJA TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING - FIRDAUS ABDUL RAHMAN; BAMBANG SUPOMO (Jurnal Bisnis dan Akuntansi, 2003)
The relationship between budgetary participation and budgetary slack and relationship between job involvement and budgetary slack has been examined in several accounting studies with conflicting results. The conflicting evidence may reflect the influence of a contingent variable. This study examined influence of organizational commitment as moderating variable in the relationship between budgetary participation and budgetary slack, and influence of organizational commitment as moderating variable in the relationship between job involvement and budgetary slack. This study provides empirical evidence that motivational factors of organizational commitment, job involvement and budgetary participation might be important factor in explaining managers propensities to create budgetary slack. The results indicate that for highly commited managers, budgetary participation is associated with decreased prospensity to create budgetary slack. For managers who have low levels of commitment to organization’s goals and values, budgetary participation is associated with increased propensity to create budgetary slack. Likewise, for highly commited managers, job involvement is associated with decrease propensity to create budgetary slack. For managers who have low levels of comittment organization’s goals and values, job involvement is associated with increased propensity to create budgetary slack.